Encuesta a los escritores argelinos - Ágreda Burillo, Fernando de (Miscelánea de Estudios Árabes y Hebraicos. Sección Árabe-Islam, 2013)
Three contemporary Algerian poets in Arabic language: Muhammad al-`Id, Abu l- Qasim Jammar y Muhammad al-Ajdar Ben `Abd al-Qadir al-Sa’ihi, give answers to an enquiry about the following subjects: A. Biography and personal facts, B. Literary activities of the autor y C. General literary subjects.